Population density, human-crocodile conflict and genetic variation among saltwater crocodile, crocodylus porosus in Sarawak - Mohd. Izwan Zulaini, Abdul Gani (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The objective of this study aims to (i) determine the distribution and density of Crocodylus porosus in rivers of western Sarawak, (ii) assess socio-economic profile and matters related to human-crocodile conflicts within population of local peoples and (iii) analyze genetic variations of C. porosus in Sarawak based on microsatellite data. Surveys of C. porosus population had been carried out using night spotting techniques in Batang Samarahan, Sibu Laut River and Bako River. The highest mean relative density was recorded in Bako River (3.19±8.24 non-hatchling/km), followed by Sibu Laut River (0.77±0.51 non-hatchling/km) and Batang Samarahan (0.60±0.33 non-hatchling/km). Pilot study showed that dependency of local communities toward rivers and their awareness toward crocodile issues are relatively high. Based on microsatellite data using Cj127 primer, result showed limited success on determining the relationship among C. porosus from different areas in Sarawak. However using Cj16 primer, phylogenetic and network analysis showed distinct clades based on geographical areas. Population genetic analyses show gene flow occurs and high number of migrants per generations in population of C. porosus in Sarawak suggesting they are panmictic population.